2016
DOI: 10.1016/j.pec.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

ENRICH: A promising oncology nurse training program to implement ASCO clinical practice guidelines on fertility for AYA cancer patients

Abstract: Objective We describe the impact of ENRICH (Educating Nurses about Reproductive Issues in Cancer Healthcare), a web-based communication-skill-building curriculum for oncology nurses regarding AYA fertility and other reproductive health issues. Methods Participants completed an 8-week course that incorporated didactic content, case studies, and interactive learning. Each learner completed a pre- and post-test assessing knowledge and a 6-month follow-up survey assessing learner behaviors and institutional chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 15 publications
(18 reference statements)
0
41
0
7
Order By: Relevance
“…By offering education and training in key communication skills (e.g., asking questions, normalizing patients’ concerns), a provider-focused intervention could foster the development of positive provider beliefs (i.e., that sexual concerns are important to discuss clinically, that discussions of sexual concerns need not take long clinically), and decrease providers’ emotional discomfort in having discussions about sexual concerns. Although few prior studies have evaluated patient-provider communication interventions about cancer-related sexual concerns [41, 42], findings from this study suggest that activating patients (i.e., increasing awareness, self-advocacy, and communication skills) to discuss sexual concerns may ultimately be one of the most critical strategies for driving increased provider communication . Interestingly, some women in this study reported feeling cast aside when given referrals that did not meet their needs.…”
Section: Discussionmentioning
confidence: 90%
“…By offering education and training in key communication skills (e.g., asking questions, normalizing patients’ concerns), a provider-focused intervention could foster the development of positive provider beliefs (i.e., that sexual concerns are important to discuss clinically, that discussions of sexual concerns need not take long clinically), and decrease providers’ emotional discomfort in having discussions about sexual concerns. Although few prior studies have evaluated patient-provider communication interventions about cancer-related sexual concerns [41, 42], findings from this study suggest that activating patients (i.e., increasing awareness, self-advocacy, and communication skills) to discuss sexual concerns may ultimately be one of the most critical strategies for driving increased provider communication . Interestingly, some women in this study reported feeling cast aside when given referrals that did not meet their needs.…”
Section: Discussionmentioning
confidence: 90%
“…These findings suggest that focusing on the modifiable outcome of training could offer an encouraging direction for intervention, particularly for medical students and trainees, who lack clinical experience from which to draw. In fact, findings from several intervention studies testing either the provision of clinical symptom summaries to providers [73] or communication skills training interventions [74, 75] suggest that such approaches may offer promise in improving communication about sexual and/or fertility-related concerns.…”
Section: Discussionmentioning
confidence: 99%
“…This kind of communication training can also be helpful in increasing clinicians' understanding of patient perspectives and priorities. There appears to be a shortage of reports on educational interventions to increase health‐care providers' knowledge about FP, but promising results have been reported for an online training program found to improve knowledge about fertility risks and FP options among oncology nurses . In addition, different types of educational resources for patients have been suggested to improve patient‐provider communication about FP .…”
Section: Strategies To Overcome Challengesmentioning
confidence: 99%